LAM (Libraries, Archives, Museums) dalam preservasi pengetahuan - Anindya Ambar Wati; Rahmi Rahmi (Perpustakaan Universitas Gadjah Mada, 2021)
Introduction. This paper aims to determine the collaboration of LAM (Libraries, Archives, Museums) in implementing knowledge preservation. Methods. A systematic review with a qualitative approach was used, and the articles were selected from Google Scholar. Data Analysis. The data collection method consists of 6 (six) stages, 1) mapping the field through scoping review, 2) comprehensive search, 3) quality assessment, 4) data extraction, 5) synthesis, and 6) write-up. Results and Discussion. The results indicated that the selected journal articles covered collaborations and cooperations that have been established by LAM in the country and overseas. The strategy used was based on the objective of preventive and curative preservations of knowledge. Human resources were found as a main challenge for implementing knowledge preservation by LAM. Conclusion. Based on the findings, research in Indonesia has led to various collaborations between LAM in implementing knowledge preservation from both preventive preservation and curative approaches.